Integrated disease management in vegetable crops - Pandey, K. K.; Nagendran, K.; Tripathi, A. N.; Manjunath, M.; Rai, A. B.; Singh, B. (Indian Horticulture, 2019)
Infection of various pathogens on vegetable crops causes huge loss of quantity and quality both in field and post-harvest conditions. In order to devise the proper management strategy, identification of diseases is very important under field conditions with their characteristic symptoms. Effective disease management can be achieved only by the integration of all the components such as cultural, biological and chemicals right from the preparation of field to the harvesting of crop. In this endeavour, ICAR-IIVR has developed some of the modules for the management of fusarial wilt, collar rot and damping off of tomato, Bhendi yellow vein mosaic virus (BYVMV) in okra, black rot of cole crops, Sclerotinia white rot and complete package for disease management in chilli.